Secretome Analysis of Human and Rat Pancreatic Islets Co-Cultured with Adipose-Derived Stromal Cells Reveals a Signature with Enhanced Regenerative Capacities - Erika Pinheiro-Machado; Bart J. de Haan; Marten A. Engelse; Alexandra M. Smink (Cells)
Pancreatic islet transplantation (PIT) is a promising treatment for type 1 diabetes (T1D) but faces challenges pre- and post-transplantation. Co-transplantation with mesenchymal stromal cells (MSCs), known for their regenerative properties, has shown potential in improving PIT outcomes. This study examined the secretome of islets cultured alone compared to the secretomes of islets co-cultured with adipose-derived stromal cells (ASCs), a subtype of MSCs, under transplantation-relevant stressors: normoxia, cytokines, high glucose, hypoxia, and combined hypoxia and high glucose. Islet co-culture with ASCs significantly altered the proteome, affecting pathways related to energy metabolism, angiogenesis, extracellular matrix organization, and immune modulation. Key signaling molecules (e.g., VEGF, PDGF, bFGF, Collagen I alpha 1, IL-1α, and IL-10) were differentially regulated depending on culture conditions and ASC presence. Functional assays demonstrated that the co-culture secretome could enhance angiogenesis, collagen deposition, and immune modulation, depending on the stress conditions. These findings highlight possible mechanisms through which ASCs may support islet survival and function, offering insights into overcoming PIT challenges. Moreover, this work contributes to identifying biomarkers of the post-transplantation microenvironment, advancing therapeutic strategies for T1D and regenerative medicine.